DIVERSIFICATION OF FOREIGN TRADE RELATIONS BETWEEN AFRICAN COUNTRIES AND RUSSIA - A. Sapuntsov (Вестник университета)
The structural analysis of export-import operations represented by the broad economic categories has been conducted in the article. The current state of foreign trade between Russia and the African states has been evaluated. The main trends of contemporary economic situation in African countries, determinants of foreign economic specialization have been identified, and their prerequisites of participation in international trade agreements have been generalized. The imperatives for diversification of trade ties between Russia and African countries have been formulated, including enhancement of economic institutions for facilitation of foreign trade and increases in shipments of manufactured goods. Such goods need to be adapted to the African market.